Determining intrinsic stress and strain state of fibre-textured thin films by X-ray diffraction measurements using combined asymmetrical and Bragg-Brentano configurations. (5th November 2019) - Motazedian, Fakhrodin; Wu, Zhigang; Zhang, Junsong; Samsam Shariat, Bashir; Jiang, Daqiang; Martyniuk, Mariusz; Liu, Yinong; Yang, Hong
Abstract: Measuring intrinsic macro stresses in fibre-textured thin films have always been challenging. Due to the nature of preferential orientation in these films, only d -spacings aligned with the film surface are observable in Bragg-Brentano X-ray diffraction scans, and to collect sufficient diffraction data needed for the stress calculation, a sample stage with tilt capabilities is essentially required. In this article, a new method is developed to lift this requirement. Based on the thin film crystal structure, an incident angle for asymmetrical XRD configuration is calculated to reveal tilted planes belonging to the same group of crystallites which are the textured majority. Measurement of d -spacing for this angle of incidence in combination with the Bragg-Brentano configuration is shown to successfully extract stress-free lattice parameter and the internal stress of the cubic metallic thin film. This method can also be adapted to determine stress and strain in polycrystalline thin films. Graphical abstract: Unlabelled Image Highlights: A new method is proposed to calculate equibiaxial internal stress of fibre-textured thin films. Using Bragg-Brentano and asymmetrical XRD configurations eliminates the need for tilting sample stage and special optics. Incident angles for asymmetrical XRD setup are calculated for textured cubic metallic films to reveal extra d-spacing data. This approach enables extraction of stress-free lattice size and elastic strain components of stressed thin films. The internal stresses of W, Fe, Nb and Pd films determined by this method agree with the values obtained by Stoney equation.